Adoption of Internet of Medical Things (IoMT) as an opportunity for improving public health in Latin America (2018)
Over the past 50 years, public health in Latin America has walked through significant changes on social and economic aspects. Since the 90's, governments from the region have performed different health reforms to improve equity, effectiveness and geographical coverage. Although, positive results have been achieved historically, strong and sustainable public health strategies are still needed to guarantee quality service. In that sense, integration of novel devices for monitoring and alerting patients about their physical health stands as a promising option for improving Latin American healthcare systems by upgrading facilities to be able to attend patients remotely, avoid care units overcrowding, guarantee real-time supervision, operational cost reduction, rapid patient attention, and lower investment on expansion of existing areas. Healthcare wearable technology acceptance and adoption barriers were investigated. It was found that most wearables are developed and promoted in developed countries with no headquarters in Latin America. This situation decreasing interest for its adoption by Latin American governments due to poor technical support, high prices, and few distribution channels. Four main barriers for wearable technology adoption were identified as: i) critical data management, security and privacy issues, ii) unreliable results accuracy, iii) unaffordable technology for low-income groups, and iv) lack of clear regulations. Based on the adoption barriers, healthcare wearable technology challenges were identified and presented. The main challenges found were: access to health service, training and distribution of human resources in health, inequalities in health, and financial schemes for health systems. It can be concluded that smart wearables in the healthcare sector could be considered as part of the solution to guarantee proper quality service and coverage in remote areas where no service is currently offered. © 2018 AISTI.